Redefining Education Landscape with Robotic Process Automation - Murali M., Selvanathan N., Archana Stephen, Balaji Saravanan U. K. (International Journal of Control and Automation, 2020)
World revolves with a focus on how things can be automated for more productivity. Robotic Process Automation (RPA) helps in the fruitful utilization of valuable man hours by allowing software robots do mundane tasks. The implementation of RPA in many universities across the globe is incrementally increasing with realization in automating admissions, teaching and examination processes. This paper shows how robots help redefine education by several use case analysis. An instance of software robots is deployed to help faculty to efficiently communicate the progress of students with parents. The robot structures the data similar to a hard copy of the progress report and forwards the compiled file. The automation was performed over individual student’s data gathered for progress report generation. The result shows how simple and efficient is the RPA to handle repetitive tasks and are done more accurately compared to manual process.